ANALYSIS BIOECONOMY, GROWTH AND RECOVERY STANDS FELLING FORESTS BASED ON LOCAL WISDOM IN PENAJAM PASER UTARA REGENCY EAST KALIMANTAN PROVINCE - Ahmad Yamani; Abubakar M Lahjie; B D.A.S Simorangkir; Rochadi Kristiningum (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
The purpose of this research are 1) to find out the increment of former forest of dipterocarpaceae and non dipterocarpaceae, 2) to know the increment of dipterocarpaceae as recovery plant at PT ITCI Kartika Utama, East Kalimantan Province, RSSI or Indonesia restoration silvicultural system as a method. The object of this research are the increment of dipterocarpaceae and non-dipterocarpaceae, while as the recovery plant is Shorea johorensis (plot A) and Dryobalanops aromatic (Plot B). The research method used theory production and increment (CAI and MAI). The data got since 2004. It was at the age 10 years while conducted predictions and simulation at the age 50 years. Simulation and production analysis used linier regression method. The result of this research showed increment od dipterocapaceae is 1.33 m³/ha/y (plot A),1.28 m³/ha/y( plot B), and the increment of non dipterocarpaceae is 1.49 m³/ha/y (plot A),1.36 m³/ha/y (plot B) at the age 30 years after logging, meanwhile the increment of recovery plant is 3.6 m³/ha/y (plot A), 2.45 m³/ha/y (plot B) at the age 40 as long as cultivation. The value of bioeconomy and the environment based on local wisdom is 35%. It is higher than market price or goverment price license. It means the value of DR and PSDH should be high because market price is not match with refund of environmental services. Key words: Bio economy, Growth, Logged, Recovery